A frameshift peptide neoantigen-based vaccine for mismatch repair-deficient cancers: a phase I/IIa clinical trial - Kloor, Matthias; Reuschenbach, Miriam; Pauligk, Claudia; Heider, Julia; Rafiyan, Mohammad-Reza; Batran, Salah-Eddin al-; Tariverdian, Mirjam; Jäger, Elke; Knebel Doeberitz, Magnus von (Clinical cancer research, 2020)
Purpose: DNA mismatch repair (MMR) deficiency is a hallmark of Lynch syndrome, the most common inherited cancer syndrome. MMR-deficient cancer cells accumulate numerous insertion/deletion mutations at microsatellites. Mutations of coding microsatellites (cMS) lead to the generation of immunogenic frameshift peptide (FSP) neoantigens. As the evolution of MMR-deficient cancers is triggered by mutations inactivating defined cMS-containing tumor suppressor genes, distinct FSP neoantigens are shared by most MMR-deficient cancers. To evaluate safety and immunogenicity of an FSP-based vaccine, we performed a clinical phase I/IIa trial (Micoryx). - Patients and Methods: The trial comprised three cycles of four subcutaneous vaccinations (FSP neoantigens derived from mutant AIM2, HT001, TAF1B genes) mixed with Montanide ISA-51 VG over 6 months. Inclusion criteria were history of MMR-deficient colorectal cancer (UICC stage III or IV) and completion of chemotherapy. Phase I evaluated safety and toxicity as primary endpoint (six patients), phase IIa addressed cellular and humoral immune responses (16 patients). - Results: Vaccine-induced humoral and cellular immune responses were observed in all patients vaccinated per protocol. Three patients developed grade 2 local injection site reactions. No vaccination-induced severe adverse events occurred. One heavily pretreated patient with bulky metastases showed stable disease and stable CEA levels over 7 months. - Conclusions: FSP neoantigen vaccination is systemically well tolerated and consistently induces humoral and cellular immune responses, thus representing a promising novel approach for treatment and even prevention of MMR-deficient cancer.